ANALISIS LAPORAN KEUANGAN DALAM MENILAI KINERJA KEUANGAN PT ULTRA JAYA MILK INDUSTRY AND TRADING COMPANY Tbk - Rahmat Yuliansyah; Marisa Helen (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This study aims to analyze the financial performance of PT Ultrajaya Milk Industry & Trading Company Tbk during the period 2020–2024. Financial performance analysis is conducted using financial ratios, including liquidity, solvency, activity, and profitability ratios. The research method applied in this study is a descriptive quantitative approach using financial ratio analysis and trend analysis. The data used are secondary data obtained from the published annual financial statements of PT Ultrajaya Milk Industry & Trading Company Tbk. The results of the study indicate that the company’s liquidity ratios are in a very good condition, reflecting its strong ability to meet short-term obligations. Solvency ratios show a healthy capital structure with a relatively low level of debt dependency. Activity ratios indicate an improvement in asset and receivable management efficiency, although inventory management still requires further optimization. Meanwhile, profitability ratios demonstrate the company’s ability to generate profits at a relatively good level, despite fluctuations caused by increased operational and production costs. Based on the trend and pattern analysis of financial ratios during the research period, it can be concluded that the financial performance of PT Ultrajaya Milk Industry & Trading Company Tbk experienced significant changes over time. Therefore, the null hypothesis (H0) is rejected, and the alternative hypothesis (Ha) is accepted. The findings of this study are expected to provide useful insights for company management, investors, and other stakeholders in decision-making processes.